Composite silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

CN122992073APending Publication Date: 2026-10-27HEFEI GUOKE CARBON CORE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611457808.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]针对现有硅碳负极碳载体孔径单一、纳米硅分散不均、硅碳界面离子传导弱、单层包覆缓冲效果有限、循环稳定性差,以及传统MXene改性硅碳存在片层堆叠、仅外部包覆、界面结合差、无法协同离子电子传导、难以量产等缺陷,本发明的第一目的是提供一种复合硅碳负极材料;本发明的第二目的是提供该复合硅碳负极材料的制备方法;本发明的第三目的是提供包含该复合硅碳负极材料的锂离子电池

Benefits of technology

1.本发明通过在多级连通孔道内壁原位生长单层或少层无堆叠的二维导电层,并利用共价键将其牢固锚定于碳骨架上,解决了传统外部包覆或物理混合方式导致的孔道内部导电盲区问题。二维导电层的高导电性与多孔碳基体协同,实现了颗粒内部每一处纳米硅均与导电网络紧密接触,显著降低了材料整体内阻。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a kind of composite silicon-carbon negative electrode material and its preparation method and lithium ion battery, belong to lithium ion battery technical field, comprising: porous carbon matrix with multiple interconnected channels inside;Two-dimensional conductive layer in-situ grown in the inner wall of multiple interconnected channels and anchored to porous carbon matrix by covalent bond;Silicon-based active material deposited in multiple interconnected channels and forming covalent interface with two-dimensional conductive layer;Fast ion conductor film continuously coated on two-dimensional conductive layer, silicon-based active material and channel inner wall;Conductive carbon coating layer coated on the outer surface of porous carbon matrix.The application constructs electron-ion double continuous transmission network, eliminates internal conductive island, significantly improves cycle stability and fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a composite silicon-carbon anode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries have been widely used in new energy vehicles, portable electronic devices, and large-scale energy storage power stations. The market is constantly demanding upgrades in battery energy density, cycle life, fast charging performance, and low-temperature performance. The theoretical lithium intercalation capacity of traditional graphite anodes is only 372 mAh / g, and the actual capacity limit of commercial graphite anodes is 360-365 mAh / g. The potential for energy density improvement has reached a theoretical bottleneck and cannot meet the development needs of next-generation high-endurance power batteries, 4680 large cylindrical batteries, and high-rate fast-charging batteries.

[0003] Silicon-based materials theoretically possess a lithium intercalation capacity of up to 4200 mAh / g, more than 10 times that of graphite anodes, demonstrating the potential to significantly improve battery energy density by replacing graphite. However, elemental silicon undergoes a massive volume expansion of approximately 380% during lithium-ion insertion / extraction, leading to three fatal flaws: First, during charge-discharge cycles, silicon particles continuously pulverize and break down, losing their conductive network connections and causing rapid deterioration of the active material; second, after silicon particles break down, they continuously expose fresh surfaces, leading to repeated decomposition of the electrolyte to form a thick and unstable SEI film, consuming electrolyte and active lithium ions, resulting in low initial coulombic efficiency and severe capacity decay; third, silicon has extremely low intrinsic electronic conductivity (10⁻⁶ mAh / g). -4 (S / cm level), pure silicon anodes have poor rate performance and cannot be adapted to fast charging scenarios.

[0004] To mitigate silicon expansion defects, the mainstream technical approach in the industry is silicon-carbon composite modification. Existing solutions can be categorized into four types: The first type is a mechanical powder mixing composite process, which physically mixes nano-silicon powder, graphite, pitch, and resin carbon source through high-speed ball milling followed by high-temperature carbonization. This process has simple equipment, but the nano-silicon only adheres to the outer surface of the carbon material, lacking pore confinement. After charge-discharge expansion, the silicon is easily peeled off, and the silicon-carbon interface is only physically bonded, resulting in high interfacial impedance. The second type is a porous silicon plus external carbon coating scheme. Porous silicon has extremely low mechanical strength, and the framework collapses directly after multiple cycles. The carbon coating layer only wraps the outer layer of the particles; after the carbon shell cracks, the material rapidly degrades. The first type is effective, but the preparation process is complex and the pickling waste liquid causes significant pollution. The second type is single mesoporous carbon-supported silicon material, which uses a single-pore-size mesoporous carbon carrier to deposit silicon via CVD vapor phase deposition. The pore connectivity is poor, and the pores are easily blocked during silicon deposition, resulting in polarized silicon distribution. Moreover, relying solely on carbon coating modification limits the lithium-ion conduction rate, and polarization is severe under fast charging conditions. The third type is carbon coating plus single fast-ion conductor surface modification technology. The modification layer only adheres to the outer surface of the material and cannot improve the lithium-ion conduction performance of the internal pores of the carbon carrier and the interface of silicon particles. Furthermore, the coating is prone to falling off during powder processing and electrode rolling, resulting in poor sustainability of the modification effect.

[0005] In recent years, the industry has introduced two-dimensional MXene (general formula Mn+1XnTx, typical Ti3C2T). x Modified silicon-based anode, utilizing its high metallic conductivity (10) 4 ~10 5 While the MXene composite silicon-carbon scheme offers advantages such as improved conductivity and expansion issues due to its two-dimensional layered flexible buffer structure and abundant -OH / -O / -F functional groups, it generally suffers from the following shortcomings: First, MXene is only physically coated externally and cannot penetrate the porous carbon channels. The nano-silicon particles within these channels lack MXene conductive contact, resulting in severe conductive islanding in the internal silicon region. Second, the MXene layers are severely stacked, blocking the interlayer conductive channels. This stacking significantly reduces the specific surface area and active sites, resulting in only point contact between the stacked MXene and silicon particles, leading to weak interfacial bonding. Third, MXene lacks chemical bond anchoring at the silicon-carbon interface, causing separation of the two phases under repeated expansion and contraction during charge and discharge, resulting in a continuous increase in interfacial charge transfer impedance. Fourth, MXene and fast ion conductors are layered independently, lacking a synergistic ion-electron conduction network. The two systems are disconnected, failing to form an integrated continuous charge transport pathway. Fifth, the MXene composite process is only a laboratory-scale intermittent route, with extremely low solid content (≤5%) during liquid-phase exfoliation and dispersion, high drying energy consumption, and large batch-to-batch variations, making it difficult to scale up to mass production lines.

[0006] In summary, there is currently no integrated silicon-carbon anode material with a multi-level interconnected porous carbon substrate, uniformly confined composite nano-silicon inside the pores, simultaneous introduction of fast ion conductors at the silicon-carbon interface, in-situ growth of non-stacked MXene inside the pores to form an electron-ion dual continuous transport network, and its complete preparation process. Summary of the Invention

[0007] To address the shortcomings of existing silicon-carbon anode carbon carriers, such as single pore size, uneven dispersion of nano-silicon, weak ion conduction at the silicon-carbon interface, limited buffering effect of single-layer coating, and poor cycle stability, as well as the defects of traditional MXene-modified silicon-carbon, such as layer stacking, only external coating, poor interfacial bonding, inability to coordinate ion and electron conduction, and difficulty in mass production, the first objective of this invention is to provide a composite silicon-carbon anode material; the second objective of this invention is to provide a method for preparing the composite silicon-carbon anode material; and the third objective of this invention is to provide a lithium-ion battery containing the composite silicon-carbon anode material.

[0008] In a first aspect, the present invention provides a composite silicon-carbon anode material, wherein the silicon-carbon anode material is a micron-sized spherical composite particle, and each particle has a functional composite structure, including: a porous carbon matrix layer, a two-dimensional conductive layer, a silicon-based active material layer, a fast ion conductor thin film layer, and a conductive carbon coating layer. The porous carbon matrix layer has multi-level interconnected channels inside; The two-dimensional conductive layer is grown in situ on the inner wall of the multi-level interconnected channels and is anchored to the porous carbon matrix layer by covalent bonds. The silicon-based active material layer is confined and deposited within the multi-level interconnected channels after the growth of the two-dimensional conductive layer, and forms a covalent interface with the two-dimensional conductive layer. The fast ion conductor thin film layer is continuously coated on the surface of the two-dimensional conductive layer, the surface of the silicon-based active material, and the inner wall of the multi-level interconnected channels.

[0009] This invention, by growing a two-dimensional conductive layer in situ on the inner wall of a multi-level interconnected channel and anchoring it with covalent bonds, differs from traditional external physical coating or liquid phase impregnation processes. This ensures the uniform distribution and non-stacked state of the two-dimensional conductive layer within the channel, eliminating internal conductive islands. At the same time, the continuous coating of the fast ion conductor film across the entire domain constructs a dual continuous electron-ion transport channel. Combined with the protection of the outer conductive carbon coating layer, this significantly improves the material's cycle stability and fast-charging performance.

[0010] Specifically, the multi-level interconnected channels are not simply a stacking of single-sized pores, but a three-dimensional hierarchical network structure formed by the interconnection of macropores, mesopores, and micropores. This multi-level channel design achieves precise functional division at the microscopic level: macropores serve as rapid diffusion channels for gaseous precursors and reaction products, ensuring that reactants can uniformly penetrate deep into the particles in subsequent processes; mesopores provide ample internal space, serving as the main loading site for silicon-based active materials and reserving necessary buffer margins for the volume expansion of silicon during charging and discharging; micropores constitute the intrinsic conductive network of the carbon skeleton and provide additional lithium storage sites. The organic interconnection of the three levels of channels fundamentally ensures the continuity of mass transfer and conductivity within the material, avoiding the problem of decreased utilization of active materials due to channel blockage.

[0011] The two-dimensional conductive layer is grown in situ on the inner wall of a multi-level interconnected channel and anchored to the porous carbon matrix via covalent bonds. It should be understood that in-situ growth here refers to the direct chemical bonding of the two-dimensional conductive layer onto the inner surface of the channel wall, rather than attachment through post-processing methods such as physical coating, impregnation, or mechanical mixing. This in-situ synthesis mechanism ensures that the two-dimensional conductive layer can uniformly spread according to the complex morphology of the channel, completely eliminating the technical defects common in traditional external coating processes, such as layer stacking, agglomeration, and inability to penetrate deep into micro-channels. Simultaneously, covalent anchoring means that a strong chemical bond is formed between the two-dimensional conductive layer and the porous carbon matrix, rather than relying solely on weak interactions such as van der Waals forces. This strong interfacial bonding effectively resists the enormous volume expansion stress generated during repeated lithium insertion / extraction processes in silicon-based anodes, preventing the conductive layer from peeling off from the carbon skeleton, thereby maintaining the long-term integrity and stability of the three-dimensional electron transport network within the particle.

[0012] Silicon-based active materials are confined and deposited within the walls of hierarchical interconnected channels and the gaps between nanosheets of the two-dimensional conductive layer, forming a covalent interface with the two-dimensional conductive layer. Specifically, the confined deposition utilizes the spatial constraint effect of the hierarchical channels, allowing the silicon-based active materials to be uniformly dispersed and grown in the form of nanocrystals within the channels, effectively suppressing excessive growth and aggregation of silicon particles. Because the silicon is confined within the channel cavity, its volume expansion is physically restrained by the pore walls, thus significantly mitigating macroscopic particle pulverization and electrode structure damage. More importantly, the covalent interface formed between the silicon-based active materials and the two-dimensional conductive layer creates a tight contact at the atomic scale. This chemically bonded interface not only significantly reduces the electron transport barrier between silicon and the conductive layer, improving reaction kinetics, but also further enhances the overall mechanical strength of the composite structure. This allows the silicon particles to remain firmly anchored to the conductive network even after hundreds or even thousands of volume expansion and contraction cycles, avoiding deactivation of the active materials due to interface separation.

[0013] A fast-ion conductor film is continuously coated on the surface of the two-dimensional conductive layer, the surface of the silicon-based active material, and the inner walls of the multi-level interconnected channels. The fast-ion conductor film is not merely present on the outer surface of the particle or in a localized area, but rather achieves full coverage of all solid-phase interfaces within the channels. This continuous coating feature microscopically constructs a high-speed lithium-ion transport channel penetrating the entire particle, solving the bottleneck problems of low ionic conductivity of the carbon matrix and high charge transfer impedance at the silicon-carbon interface in traditional silicon-carbon anode materials. When lithium ions are inserted, they can rapidly migrate to the surface of the silicon-based active material through this continuous fast-ion conductor film to participate in the reaction, without relying on a slow solid-phase diffusion process. Simultaneously, this film also acts as an artificial SEI film, effectively isolating the electrolyte from direct contact with the internal active material, suppressing side reactions, and thus improving the material's initial coulombic efficiency and cycle life. It should be understood that the fast-ion conductor film and the two-dimensional conductive layer are spatially intertwined, jointly forming an electron-ion dual continuous cooperative transport network, which is the key structural basis for achieving high-rate charge-discharge performance.

[0014] A conductive carbon coating layer is applied to the outer surface of a porous carbon matrix. As the outermost protective barrier of the composite material, the conductive carbon coating layer plays a three-fold role: first, it fills and seals the open pores on the outer surface of the porous carbon matrix, preventing excessive electrolyte penetration and unnecessary side reactions, and stabilizing the solid electrolyte interface film; second, it provides a smooth and dense particle surface, improving the material's processing flowability and electrode compaction density; and third, it enhances the electron conductivity between particles, reducing the overall contact resistance of the electrode. Through the synergistic effect of the above-mentioned functional composite structure, the multi-level porous confined silicon-based anode composite material provided in this embodiment successfully achieves simultaneous improvements in high capacity, long cycle life, and fast charging performance.

[0015] Preferably, the porous carbon matrix layer simultaneously comprises interconnected macropores, mesopores, and micropores, with the porous carbon having a D50 of 5–15 μm and a specific surface area of ​​600–2400 m². 2 / g, total pore volume is 0.8–2.2 cm³ 3 / g.

[0016] Preferably, the pore size of the macropores is 50–200 nm, the pore size of the mesopores is 2–50 nm, and the pore size of the micropores is 0.35–2 nm; the micropores account for 5–100% of the total pore volume, the mesopores account for 5–100% of the total pore volume, and the macropores account for 5–50% of the total pore volume, with the sum of the three percentages being 100%.

[0017] Preferably, the porous carbon matrix is ​​a low-defect graphitized hard carbon / soft carbon composite carbon with a graphitization degree R of 0.3 to 0.8 and an electronic conductivity ≥12 S / cm.

[0018] By adopting the above technical solutions, the three-level channels work together: macropores serve as gas-phase diffusion channels for silicon deposition gas and MAX precursor, ensuring that gas molecules uniformly penetrate into all channels inside the powder particles; mesopores provide the main silicon confined space, providing a buffer margin for the expansion of nano-silicon; and micropores construct a continuous electronic conductive network, improving the intrinsic conductivity of the carbon framework.

[0019] Preferably, the two-dimensional conductive layer comprises Ti3C2T x MXene nanosheets are bonded to a porous carbon matrix via covalent bonds Ti-OC.

[0020] Preferably, the thickness of the MXene nanosheets is 1–5 nm and the lateral dimension is 1–80 nm.

[0021] By adopting the above technical solutions, monolayer / few-layer Ti3C2T is grown in situ on the inner wall of all porous carbon interconnected channels. x MXene ultrathin nanosheets, 1-5 nm thick, 1-80 nm lateral dimension; MXene is firmly bonded to the inner wall of carbon channels through Ti-OC covalent bonds, without layer stacking or agglomeration; MXene is uniformly distributed on the inner walls of all mesopores and macropores, constructing a three-dimensional continuous metallic conductive network inside the channels, and MXene does not block the pores, completely preserving the original silicon expansion buffer space.

[0022] In this application, the specific functions of MXene include: ① utilizing the high conductivity of MXene at the metallic level to completely eliminate conductive islands of nano-silicon within the channels, achieving full-domain electron conduction within the particles; ② the two-dimensional flexible layered structure can adaptively buffer the radial expansion of silicon during charging and discharging, dispersing localized stress concentration and protecting the carbon skeleton from microcracks; ③ the abundant -OH, -O, and -F functional groups on the MXene surface provide a large number of uniform anchoring points, providing a substrate for the subsequent in-situ uniform growth of nano-silicon and fast-ion conductors; ④ the MXene lithiophilic interface significantly reduces the lithium-ion migration barrier, significantly improving low-temperature lithium storage and fast-charging performance.

[0023] Preferably, the silicon-based active material includes silicon nanocrystals, which are uniformly and confinedly deposited in the internal interconnected channels modified with MXene. The original particle size of the silicon nanocrystals is 0.1–120 nm, and a Ti-O-Si covalent interface is formed between the silicon nanocrystals and the MXene nanosheets.

[0024] By adopting the above technical solutions, nano-silicon grains can be uniformly deposited and anchored on the inner walls of all the through-holes of the multi-level porous carbon matrix and inside the gaps between MXene nanosheets. The particle size is 0.1-120 nm and will not cause silicon agglomeration. The nano-silicon completely fills the pore cavities after being coated with MXene, with almost no silicon exposed on the outer surface of the carbon particles. The silicon grains are closely bonded to the MXene nanosheets, and stable Ti-O-Si chemical bonds are generated in situ during charging and discharging. The two-dimensional MXene layer completely wraps and binds the sides of the silicon particles, and together with the three-dimensional carbon skeleton, it restricts the volume expansion of silicon, thus preventing silicon pulverization, shedding, and detachment from the conductive skeleton from the root.

[0025] Preferably, the thickness of the fast ion conductor thin film layer is 1 to 6 nm, and the material of the fast ion conductor thin film layer includes at least one of lithium phosphorus oxynitride (LiPON), lithium titanium phosphate (LTP), lithium aluminum phosphate (LAP), or lithium lanthanum zirconium (LLZO).

[0026] By adopting the above technical solutions, the room temperature lithium-ion conductivity of the fast ion conductor thin film layer is ≥10. -4 S / cm, a continuous and dense fast ion conductor thin layer of 1-6nm is simultaneously coated on the surface of all MXene wafers, the surface of nano-silicon grains, and the inner wall of porous carbon channels. The fast ion conductor thin film covers the entire MXene conductive network and silicon active interface, forming an integrated continuous dual transport channel of MXene electrons and fast ion conductor ions, which completely solves the problems of insufficient ion conduction, severe interface polarization, and fast charging lag in the traditional MXene system.

[0027] Preferably, the conductive carbon coating layer has a thickness of 10–35 nm and coats the outer surface of the micron-sized spherical composite particles.

[0028] Preferably, the conductive carbon includes at least one of pitch cracking carbon and resin carbonization carbon.

[0029] By adopting the above technical solutions, the outer carbon coating layer fills the tiny voids on the powder surface, completely isolating the electrolyte from direct contact with the internal MXene and silicon active materials, suppressing the continuous side reactions of MXene functional groups, silicon, and electrolyte, and stabilizing the SEI film structure. Simultaneously, it constructs a highly efficient conductive network between particles, further enhancing the overall electronic conductivity and structural integrity of the electrode.

[0030] Preferably, the silicon-carbon anode material comprises, by mass percentage: 10-80% porous carbon matrix layer, 0.8-4% two-dimensional conductive layer, 10-80% silicon-based active material layer, 0.5-4% fast ion conductor thin film layer, and 1.5-8% conductive carbon coating layer, with the sum of the mass percentages of each component being 100%.

[0031] Preferably, the silicon-carbon anode material of this application has a reversible capacity of 1250–2250 mAh / g; an initial charge-discharge coulombic efficiency of 90–94%; a capacity retention rate of ≥95% after 800 cycles at 1C room temperature; a capacity retention rate of ≥90.0% after 200 cycles at 5C fast charging room temperature; and an electrode compaction density of 1.5–1.8 g / cm³. 3 The internal resistance of the electrode is reduced by more than 50% compared to the four-layer system without MXene.

[0032] Secondly, the present invention provides a method for preparing a silicon-carbon anode, comprising the following steps: S1. Preparation of porous carbon matrix layer: The carbon source precursor is mixed with the pore-forming agent to form a precursor slurry, which is then spray-dried to obtain composite carbon precursor microspheres; the composite carbon precursor microspheres are pre-carbonized and shaped to obtain a carbon skeleton semi-finished product; the carbon skeleton semi-finished product is calcined with an activator to form pores, and then purified by post-treatment to obtain a porous carbon matrix. S2, Porous carbon channel alumina pre-activation modification: Alumina modification layer is deposited on the inner wall of the channel and the surface of MXene nanosheets by atomic layer deposition; S3. In-situ confined deposition of nano-silicon inside the pores: Nano-silicon grains are deposited inside the pores using chemical vapor deposition. S4. In-situ coating of fast ion conductors: A continuous fast ion conductor film is generated in-situ on the surface of nano-silicon grains, the surface of MXene nanosheets, and the inner wall of the channels. S5. Conductive carbon composite coating on the outer layer of the powder: A conductive carbon coating layer is formed on the outer surface of the particles through gas phase carbon coating and / or liquid phase carbon coating processes to obtain the silicon-carbon anode material.

[0033] Preferably, the carbon source precursor includes thermosetting phenolic resin and mesophase pitch; The pore-forming agent comprises polyethylene glycol PEG2000 and nano-calcium carbonate in a mass ratio of (1-6):(6-1); The mass ratio of the thermosetting phenolic resin, mesophase pitch and pore-forming agent is (40-70):(10-40):(1-20); The inlet air temperature of the spray dryer is 120-220℃ and the outlet air temperature is 65-120℃. The pre-carbonization and shaping temperature is 500–950℃, and the holding time is 2–8 hours; The mass ratio of the carbon skeleton semi-finished product to the activator is (1-6):(6-1), the calcination temperature is 600-1050℃, and the holding time is 1-6h; The activator comprises KOH and ZnCl2 in a mass ratio of (1-10):(10-1).

[0034] Preferably, the post-processing purification includes: repeatedly washing the activated product after calcination and pore formation with hot deionized water until the pH of the filtrate is 7 to remove residual alkali metal ions; drying, air-jet milling and sieving to obtain a porous carbon matrix with multilevel interconnected channels and a D50 value of 5-15 μm, for later use.

[0035] Preferably, in step S1, the preparation of the porous carbon matrix layer further includes the following steps: A porous carbon matrix prepared from S1 was spread evenly in a rotary vapor furnace, with a single layer thickness ≤2 mm; argon gas was continuously used to purify the furnace cavity, with the oxygen content controlled to <10 ppm, and the temperature was raised to 700–900℃; Ti3AlC2T was then introduced. x Precursor vapor, carrier gas Ar flow rate 60-120 sccm, vapor phase permeation 1.5-3 h; the precursor gas source is turned off, furnace temperature is maintained at 700-900℃, LiF-HCl composite vapor phase etching system is introduced, and etching is carried out at this temperature for 2-4 h; high-purity argon gas is continuously purged into the furnace cavity to completely remove residual etching byproducts; after purging, argon gas is continuously introduced and the furnace is naturally cooled to room temperature, and the material is discharged in a sealed manner to obtain a porous carbon matrix with an embedded MXene three-dimensional conductive network, which is preserved in complete isolation from water and oxygen.

[0036] By employing the above technical solutions, Al atoms in the MAX phase are precisely stripped using vapor-phase selective etching, while preserving the complete Ti-C framework, allowing for the in-situ generation of monolayer / few-layer Ti3C2T on the inner wall of the pores. x MXene ultrathin nanosheets: The confined pore space naturally restricts the lateral growth of MXene, completely eliminating the stacking and aggregation of sheets. Through a high-temperature dehydration condensation reaction, stable Ti-OC covalent bonds are formed between the -OH functional groups on the MXene surface and the defect sites of the carbon framework, achieving a firm anchoring of the MXene nanosheets.

[0037] Preferably, step S2 includes: placing the porous carbon substrate in an atomic layer deposition chamber, evacuating to below 5 Pa, heating to 180–320 °C, using trimethylaluminum (TMA) and water vapor as precursors, and 99.999% high-purity nitrogen as carrier gas and purge gas, and cycling 5–40 times to deposit a 0.5–4 nm alumina modification layer on the surface of MXene nanosheets and the inner wall of the pores.

[0038] By adopting the above technical solution, a cycle is completed by nitrogen purging after TMA pulse, followed by water vapor pulse and nitrogen purging. The alumina thin layer deposited on the MXene surface and all the inner walls of the channels can uniformly modify MXene and carbon substrate, improve the uniformity of active sites on the inner walls of the channels, and provide uniform anchoring points for subsequent uniform deposition of nano-silicon, Ti-O-Si bonding, and in-situ growth of fast ion conductors, avoiding silicon agglomeration caused by local rapid decomposition of silane gas.

[0039] Preferably, step S3 includes: spreading the powder obtained in step S2 in a single layer on a rotary CVD furnace boat with a layer thickness ≤2mm, replacing the oxygen content with argon until the oxygen content is <10 ppm, heating to 420-580℃ and holding for 0.5 h, introducing a mixed gas with a SiH4 to Ar volume ratio of 1:(15-40) at a gas flow rate of 50-150 sccm, and depositing for 60-400 min.

[0040] By adopting the above technical solution, silane molecules penetrate into all the interconnected channels inside the powder through the diffusion effect of multi-level pores, and decompose in situ at the active sites modified by alumina and the surface of MXene to generate 0.1-120 nm nano-silicon grains; the silicon grains grow uniformly only inside the channels and are closely bonded to MXene to form a Ti-O-Si covalent interface, and there is no large amount of free silicon precipitation on the outer surface of the powder.

[0041] Preferably, step S4 includes: transferring the powder obtained in step S3 into a plasma-assisted atomic layer deposition furnace, with a vacuum degree ≤3 Pa and a temperature of 250-400℃, and using alternating pulsed cycles of a metal-organic lithium source, a titanium source, and a phosphorus source for 5-35 cycles to generate a 1-6 nm lithium titanium phosphate fast ion conductor film in situ on the surface of the nano-silicon grains, the surface of the MXene nanosheets, and the inner wall of the pores; wherein the metal-organic lithium source is selected from one or more of LiOtBu, LiHMDS, and Lider, the titanium source is selected from one or more of Ti[NMe2]4, Ti(OiPr)4, and TiCl4, and the phosphorus source is selected from one or more of trimethyl phosphate and triethyl phosphate.

[0042] By adopting the above technical solutions, a 1-6 nm continuous dense lithium titanium phosphate (LTP) fast ion conductor film is generated in situ on the surface of all nano-silicon grains, the surface of MXene nanosheets, and the inner wall of carbon channels. The film completely fills the tiny gaps at the silicon-MXene and MXene-carbon interfaces, constructing a three-dimensional lithium-ion transport network that runs through the entire powder, forming a complete electron-ion dual continuous synergistic conduction system with the MXene electronic conduction network.

[0043] In some optional embodiments, step S4 may also include the following steps: Lithium phosphate, lanthanum nitrate, zirconium nitrate, and lithium nitrate were uniformly impregnated in the liquid phase at a molar ratio of 1.5:3:2:2.8 using an ethanol-water mixed solvent and dilute nitric acid to adjust the pH to 2.6–3.0 to form a stable suspension impregnation solution. The solid-liquid ratio was 1:(4–8), and the mixture was thoroughly stirred, sonicated for 30–60 min, and then vacuum dried. The vacuum-dried solid material was then calcined, preferably at 650–760℃, and held for 1–4 h to generate a lanthanum-zirconium-lithium (LLZO) fast ion conductor interface layer in situ under an Ar atmosphere, which is suitable for a low-cost liquid-phase mass production process.

[0044] Preferably, step S5 includes: using one or more of methane and its homologues, acetylene and its homologues, and benzene and its homologues as the carbon source gas, and one or more of helium, argon, and nitrogen as the inert gas, with the ratio of inert gas to carbon source gas being (1-10):1; the rotary kiln speed being 0.25-2.5 r / min; the heating rate being 1-10℃ / min; the deposition temperature being 500-950℃; and the deposition time being 1-6 h. Natural cooling, airflow agitation, magnetic iron removal, and grading and sieving are then performed to obtain the final product.

[0045] In some optional embodiments, step S5 may also include the following steps: The process involves a liquid-phase carbon coating step, where the intermediate powder obtained from S4 is mixed with ethanol solvent and stirred to form a suspension with a solid content of 20-35%. A composite carbon source of asphalt powder and linear phenolic resin is then added, with the total carbon source addition amount being 2-9 wt% of the powder mass. The mixture is stirred at high speed for 2-4 hours and then ultrasonically dispersed to ensure uniform adsorption of the carbon source onto all outer surfaces of the powder. The suspension is then spray-dried at an inlet air temperature of 145℃ and an outlet air temperature of 75℃ to obtain a silicon-carbon composite precursor powder uniformly coated with the carbon source. The precursor powder is then placed in a rotary carbonization furnace under argon protection, with a heating rate of 1-5℃ / min, and held at 560-1100℃ for 6-8 hours. The asphalt and resin undergo high-temperature pyrolysis and graphitization, forming a continuous, dense, conductive carbon coating layer of 10-35 nm on the outside of the powder. The powder is then naturally cooled, dispersed by airflow, magnetically removed, and graded and sieved to obtain the final product.

[0046] Thirdly, the present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; The negative electrode sheet comprises a silicon-carbon negative electrode material as described in the first aspect or a silicon-carbon negative electrode material prepared by the method described in the second aspect.

[0047] Preferably, the negative electrode further includes a conductive agent, a binder, a dispersant, and a current collector. The conductive agent includes one or a combination of graphene, carbon nanotubes, and Super P, forming a composite conductive system. The binder includes a water-based binder composed of polyacrylic acid, sodium alginate, and styrene-butadiene rubber. The dispersant includes sodium carboxymethyl cellulose (CMC). Copper foil is used as the current collector. The electrode coating surface density is 12–22 mg / cm³. 2 The compacted density is 1.5–1.8 g / cm³. 3 .

[0048] Preferably, the positive electrode includes ternary NCM811, the separator includes a polyethylene / polypropylene composite ceramic separator, and the electrolyte includes a carbonate-based lithium salt electrolyte. This battery can be used as a power battery for new energy vehicles, an energy storage battery, and a high-rate lithium battery for consumer electronics.

[0049] The beneficial effects of this invention are: 1. This invention solves the problem of conductive blind spots inside the pores caused by traditional external coating or physical mixing methods by growing a single or few non-stacked two-dimensional conductive layer in situ on the inner wall of a multi-level interconnected channel and firmly anchoring it to a carbon framework using covalent bonds. The high conductivity of the two-dimensional conductive layer, in synergy with the porous carbon matrix, ensures that every nano-silicon particle inside the particle is in close contact with the conductive network, significantly reducing the overall internal resistance of the material.

[0050] 2. The fast ion conductor film of the present invention is continuously coated over the entire surface of the two-dimensional conductive layer, the silicon-based active material, and the inner wall of the pores. The electron transport network formed by the film and the two-dimensional conductive layer interweaves and intersects, constructing a continuous electron-ion transport channel that runs throughout the entire particle. This synergistic structure significantly reduces the interfacial charge transfer impedance and improves the lithium-ion migration rate, thereby significantly improving the rate performance and low-temperature discharge performance of the material.

[0051] 3. The two-dimensional conductive layer of this invention forms a bicovalent interface with Ti-OC bonds and Ti-O-Si bonds between itself and the porous carbon matrix and silicon-based active material, respectively. The bonding force is much stronger than physical adsorption, effectively resisting the volume expansion stress during charge and discharge and preventing the active material from pulverizing and falling off. At the same time, the flexible sheet structure of the two-dimensional conductive layer and the macroscopic buffer space of the multi-level pores work synergistically to further disperse local stress, protect the integrity of the SEI film, and significantly improve the first-efficiency and long-cycle retention rates.

[0052] 4. This invention employs a continuous, end-to-end vapor-phase preparation process, suitable for industrial mass production. The preparation method utilizes vapor-phase precursor infiltration and vapor-phase selective etching to synthesize a two-dimensional conductive layer in situ, eliminating the high pollution, low solids content, and easy stacking defects of traditional liquid-phase stripping. This process can be seamlessly integrated with subsequent CVD deposition, ALD coating, and other processes, achieving fully enclosed continuous production with good batch consistency, low environmental costs, and solving the problem of the difficulty in large-scale mass production of high-performance modified silicon-carbon anodes. Detailed Implementation

[0053] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0054] Example Example 1: A composite silicon-carbon anode material was prepared by the following method: Preparation of S1 multi-level interconnected porous carbon matrix: Preparation of S101 carbon precursor composite: 600 g of thermosetting phenolic resin 2130, 300 g of mesophase pitch ZLQ-601, 100 g of PEG2000 and nano-CaCO3 composite pore-forming agent in a mass ratio of 3:2, 2 L of anhydrous ethanol were added, and the mixture was stirred at 50℃ for 2 h to form a homogeneous slurry; spray drying was carried out at an inlet air temperature of 160℃ and an outlet air temperature of 85℃ to obtain spherical composite precursor microspheres with a D50 of 10 μm; S102 Pre-carbonization and shaping: The composite microspheres are placed in a rotary carbonization furnace under high-purity nitrogen (99.99%) protection, with a heating rate of 3℃ / min, and the temperature is raised to 650℃ and held for 4 h. Pre-carbonization removes small molecule volatiles and forms a stable carbon skeleton semi-finished product.

[0055] S103 graded activation pore formation: KOH and ZnCl2 with a mass ratio of 7:3 (pre-carbonized powder and solid composite activator) are mixed uniformly by dry method at a mass ratio of 1:2.5 (material-agent ratio); the mixture is transferred to a closed tube furnace under argon atmosphere, heated to 850℃ at 5℃ / min and held for 3 hours; the dual activators are etched stepwise at high temperature: ZnCl2 is etched at low temperature to generate macropores and mesopores, and KOH is etched at high temperature to generate micropores, forming an in-situ interconnected three-level pore network.

[0056] S104 post-processing purification: The activated product was repeatedly washed with hot deionized water (60℃) until the pH of the filtrate was 7 to remove residual alkali metal ions; vacuum dried at 80℃ for 12 h; air-jet pulverization and sieving were performed to obtain a porous carbon matrix PC with multilevel interconnected channels and a D50 value of 8 μm, which was then set aside for later use.

[0057] S2 channel pre-activated alumina modification: PC powder prepared from S1 was placed in an ALD atomic layer deposition chamber; the chamber was evacuated to below 5 Pa; the deposition temperature was 220℃; the precursors were TMA and water vapor; the carrier gas / purge gas was 99.999% high-purity N2; the cycle was repeated 10 times (TMA pulse → N2 purge 1 → water vapor pulse → N2 purge 2 constitutes one standard cycle; where TMA pulse: 0.3 s; purge 1: 20 s; H2O pulse: 0.3 s; purge 2: 20 s; single cycle growth rate GPC≈0.10 nm / cycle), and a 1 nm alumina modification layer was deposited on the inner wall of the channel to obtain material A-PC, which was discharged and sealed for later use.

[0058] In-situ confined deposition of nano-silicon within S3 channels: The pre-activated carbon powder obtained by S2 was laid in a single layer in a rotary CVD furnace with a layer thickness of 1.5 mm. Argon gas was purged three times, and the temperature was raised to 500℃ and held for 0.5 h. A mixed gas with a volume ratio of SiH4:Ar=1:20 was introduced at a flow rate of 80 sccm and the deposition was carried out for 320 min. The silane was turned off and the gas was cooled with argon to obtain Si@PC intermediate. The average grain size of the nano-silicon was 2 nm, and it was all distributed in the internal pores of the carbon, thus obtaining the nano-silicon confined composite intermediate Si@A-PC.

[0059] S4 internal pore in-situ LTP fast ion conductor coating: 100 g of the intermediate Si@A-PC material prepared by S3 was transferred into a plasma ALD furnace under vacuum of 2 Pa and 300℃. The furnace was subjected to 18 pulsed cycles using lithium tert-butoxide (organic lithium source), tetraisopropyl titanate (titanium source), and trimethyl phosphate (phosphorus source). Each cycle included: lithium source cycle (lithium source pulse 10s → Ar purge 20s → O2 plasma treatment 10s → Ar purge 20s), titanium source cycle (titanium source pulse 3s → Ar purge 20s → O2 plasma treatment 10s → Ar purge 20s), and titanium source cycle (titanium source pulse 3s → Ar purge 20s). The process involved in-situ generation of a 3 nm lithium titanium phosphate fast-ion film inside the pores, which fully covered the silicon grains and the inner walls of the carbon pores, resulting in the fast-ion modified intermediate LTP-Si@A-PC.

[0060] S5 outer conductive carbon composite coating: 1000 g of the fast ion-modified intermediate LTP-Si@A-PC was placed in a rotary kiln for gas-phase carbon coating. Acetylene was selected as the carbon source gas, and argon was selected as the inert gas. The heating rate was set to 2℃, from room temperature to 580℃, and the temperature was held at 580℃ for 2 hours. When the temperature reached 580℃, an acetylene-argon mixture was introduced. During the holding process, only the mixture was introduced. The flow rate of the acetylene-argon mixture was set to 2.4 L / min, and the acetylene-argon flow rate ratio was 1:5. The rotation speed of the rotary kiln was set to 0.5 r / min. After the holding period, the mixture was allowed to cool naturally to room temperature. Then, the material was discharged, broken up, sieved, and demagnetized to obtain the finished silicon-carbon composite material.

[0061] Example 2, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, it is kept at 800°C for 3 hours.

[0062] Example 3, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, it is kept at 900°C for 3 hours.

[0063] Example 4: A composite silicon-carbon anode material, differing from Example 1 only in that, in S3, the silicon deposition temperature is 560°C.

[0064] Example 5: A composite silicon-carbon anode material, differing from Example 1 only in that, in S3, the silicon deposition temperature is 480°C.

[0065] Example 6: A composite silicon-carbon anode material, differing from Example 1 only in that, in S3, the silicon deposition time is 280 min.

[0066] Example 7, a composite silicon-carbon anode material, differs from Example 1 only in that, in S3, the silicon deposition time is 360 min.

[0067] Example 8, a composite silicon-carbon anode material, differs from Example 1 in that liquid-phase impregnation and calcination are used instead of S4, specifically including the following: Lithium nitrate, titanium nitrate, and ammonium dihydrogen phosphate were dissolved in ethanol to prepare an impregnation solution. Si@PC powder was vacuum impregnated for 2 h, dried at 120℃, and calcined at 700℃ with argon for 2 h to generate a 3 nm LTP fast ion layer inside the pores.

[0068] Example 9, a composite silicon-carbon anode material, differs from Example 1 in that liquid-phase impregnation and calcination are used instead of S4, specifically including the following: Lithium nitrate, lanthanum nitrate, and zirconium nitrate were dissolved in ethanol to prepare an impregnation solution. Si@PC powder was vacuum impregnated for 2 h, dried at 120℃, and calcined at 700℃ with argon for 2 h to generate a 3 nm LLZO fast ion layer inside the pores.

[0069] Example 10, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, the mass ratio of the composite activator KOH to ZnCl2 is 5:5.

[0070] Example 11, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, the mass ratio of composite activator KOH to ZnCl2 is 3:7.

[0071] Example 12, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, the ratio of material to composite activator is 1:1.5.

[0072] Example 13, a composite silicon-carbon anode material, differs from Example 1 only in that, in S103, the ratio of material to composite activator is 1:3.5.

[0073] Example 14, a composite silicon-carbon anode material, differs from Example 1 in that step S1 further includes S105, as follows: 100 g of hierarchical porous carbon was spread in a rotary vapor furnace to a thickness of 1.5 mm, purged three times with argon gas, and heated to 800℃; Ti3AlC2T was then introduced. x The precursor vapor for the thin film consisted of vapor derived from tetraisopropyl titanate (TTIP) as the Ti source, vapor derived from trimethylaluminum (TMA) as the Al source, and acetylene (C2H2) as the carbon source gas, with a molar ratio of 3:1:2. The total flow rate of the mixed gas was 30 sccm, and the Ar carrier gas flow rate was 90 sccm. The vapor phase permeation was carried out for 2 h. A mixture of LiF and HCl with a molar ratio of 1:1.5 was introduced for etching, and the vapor phase was held at 45℃ for 3 h to generate a monolayer of Ti3C2T within the pores through in-situ aluminum removal. x MXene was continuously purged with high-purity argon gas to completely remove residual etching byproducts. After purging, argon gas was continuously introduced and cooled to obtain MX@PC intermediate with an MXene content of 1.8 wt%. S2-S5 were the same as in Example 1.

[0074] Comparative Example Comparative Example 1: A silicon-carbon anode material was prepared by the following method: Preparation of S1 single mesoporous distributed porous carbon framework: S101 template pretreatment: Place the ultra-large pore size SBA-15 mesoporous silica powder in a vacuum oven and dry it at 120℃ for 6 hours to fully remove adsorbed moisture and impurities in the pores. After cooling, seal it for later use. Preparation of S102 RF resin precursor solution: Resorcinol and formaldehyde were completely dissolved in anhydrous ethanol at a molar ratio of 1:1.5. After stirring evenly at room temperature, an appropriate amount of ammonia was added dropwise to adjust the system to a weakly alkaline state. Stirring was continued for 20 min to obtain a low degree of polymerization, clear and transparent RF resin precursor impregnation solution. S103 Vacuum Impregnation and Filling: The pretreated SBA-15 powder is placed in a gizzard-shaped reaction flask, and the prepared RF resin precursor solution is added until the powder is completely submerged. Vacuum impregnation is carried out at room temperature for 80 min. The precursor solution is fully penetrated into the SBA-15 mesoporous channels by negative pressure. After impregnation, the free solvent is removed by low-temperature rotary evaporation to obtain the RF resin-filled SBA-15 composite precursor. S104 thermosetting treatment: The composite precursor is evenly spread and placed in an oven at 80℃ for 12 hours to ensure that the RF resin in the pores is fully cross-linked and shaped, preventing resin flow, phase separation and skeleton collapse during subsequent carbonization. S105 High-Temperature Carbonization: The cured composite powder is placed in a tube furnace and carbonized in stages under a high-purity nitrogen atmosphere: the temperature is increased to 350℃ at a rate of 2℃ / min and held for 3 hours to remove small molecule organic matter and template additives; then the temperature is increased to 650℃ at a rate of 2.5℃ / min and carbonized at a constant temperature for 4 hours, and then cooled naturally to room temperature to obtain carbon / silicon dioxide composite material.

[0075] S106 template etching: The carbon / silica composite material was etched with diluted hydrofluoric acid solution at room temperature for 24 h to remove the silica template. The solid was collected by centrifugation, washed with deionized water until neutral, and vacuum dried to obtain ordered mesoporous carbon material.

[0076] In-situ confined deposition of nano-silicon within the S2 channel: The ordered mesoporous carbon material obtained from S1 was laid in a single layer on a rotary CVD furnace with a layer thickness of 1.5 mm. Argon gas was purged three times, and the temperature was raised to 500℃ and held for 0.5 h. A SiH4:Ar=1:20 mixed gas was introduced at a flow rate of 80 sccm, and deposition was carried out for 320 min. The silane was turned off, and the argon gas was cooled to obtain the intermediate.

[0077] S3 outer conductive carbon composite coating: 1000 g of the intermediate was placed in a rotary kiln for gaseous carbon coating. Acetylene was selected as the carbon source gas and argon as the inert gas. The heating rate was set to 2°C, from room temperature to 580°C, and the temperature was held at 580°C for 2 hours. When the temperature reached 580°C, an acetylene-argon mixture was introduced. The flow rate of the acetylene-argon mixture was set to 2.4 L / min, and the acetylene-argon flow rate ratio was 1:5. The rotation speed of the rotary kiln was set to 0.5 r / min. After the holding time was completed, the mixture was allowed to cool naturally to room temperature. Then the material was discharged, broken up, sieved, and demagnetized to obtain the finished silicon-carbon composite material.

[0078] Comparative Example 2: A silicon-carbon anode material was prepared by the following method: Step S1 is the same as Comparative Example 1. After step S1, based on Example 1, the fast ion conductor coating process inside S4 is omitted, and the remaining processes are the same.

[0079] Comparative Example 3 is a silicon-carbon anode material, which differs from Example 1 only in that step S4 is not performed.

[0080] Comparative Example 4: A silicon-carbon anode material was prepared by the following method: Same as Example 14, except that step S1 is modified to prepare a porous carbon framework with a single mesoporous distribution: the same as Comparative Example 1. The in-situ MXene process in the S105 pores is omitted. Traditional liquid-phase exfoliation of Ti3C2Tx MXene powder is used, i.e., LiF is dissolved in 9 mol / L hydrochloric acid to prepare an etching solution, Ti3AlC2 powder is slowly added, and the Al layer is removed by etching with constant temperature stirring at 45°C for 24 h; the slurry is repeatedly centrifuged and washed with water until the supernatant is nearly neutral, resulting in a multilayer Ti3C2Tx MXene. x Dispersed in water, the particles were ultrasonically exfoliated in an ice-water bath; unexfoliated coarse particles were removed by low-speed centrifugation, the upper colloid was collected, and freeze-dried to obtain a few-layer Ti3C2T. x MXene will use pre-prepared few-layer Ti3C2T x MXene powder and Si@PC particles were added to a ball mill jar, and anhydrous ethanol was used as the medium and zirconia balls as the abrasive. The planetary wet ball milling speed was set to 300 rpm, and the milling time was 6 h. The mechanical shearing action caused MXene nanosheets to spread and adsorb uniformly on the surface of Si@PC particles to form a continuous film. After centrifugation, the slurry was vacuum dried to obtain MXene film-coated Si@PC composite powder. The MXene content was 1.8 wt%, and the remaining steps were the same as in Example 14.

[0081] Performance testing: 1. The S1 porous carbon framework material PC in Examples 1-14 and Comparative Examples 1-4 was subjected to fully automated specific table and pore size analysis tests. The data of several key experimental sets are statistically compared as shown in Table 1.

[0082] 2. The final silicon-carbon anode materials prepared in Examples 1-14 and Comparative Examples 1-4 were subjected to component content testing, XRD testing, and silicon grain size calculation and button cell assembly testing. The button cell assembly test included: coating formulation: active material: SP:PAA = 80%: 10%: 10%; button cell testing steps: discharge process: stand for 6 hours; discharge at 0.1C to 0.005 V, stand for 5 minutes; discharge at 0.02C to 0.005 V, stand for 5 minutes; discharge at 0.01C to 0.005 V; charging process: stand for 5 minutes; charge at 0.1C to 1.5 V. The test results of several key experimental groups were statistically compared and are shown in Table 2.

[0083] 3. Examples 1-14 and Comparative Examples 1-4 were mixed with graphite at a negative electrode specific capacity of 600 mAh / g, and then homogenized and coated at a ratio of 93:4:1.5:1.5 (negative electrode material binder: dispersant: conductive agent). Finally, they were assembled with ternary positive electrode NCM811 to form a lithium-ion soft-pack battery (design capacity of 4.5Ah), and then the electrical performance of the lithium-ion battery was tested.

[0084] 4. The capacity of the above batteries was tested at 25℃; the initial coulombic efficiency (FE) of the batteries was calculated, as well as the capacity retention rate after 800 cycles at 1C and after 200 cycles at 5C. The battery data shown are the average values ​​of at least 5 battery test results. The results are shown in Table 3.

[0085] Table 1

[0086] Table 2

[0087] Table 3

[0088] As shown in Table 1, the pore volumes of the porous carbon intermediates in Example 1 and Comparative Example 1 are similar, but their pore distributions differ. The porous carbon intermediate in Example 1 features a hierarchical pore distribution design, while Comparative Example 1 features a single mesopore distribution design. Example 14 uses the same porous carbon preparation method as Example 1. Further analysis of the electrochemical data in Table 3, comparing Example 14, Comparative Example 1, and Comparative Example 2, reveals that the lack of hierarchical channels, alumina pre-activation, and the construction of an internal fast ion interface layer significantly reduces material capacity, first-time efficiency, cycling performance, and rate capability, validating the necessity of the core structure of this invention. Further comparison of Example 1 and Comparative Example 3 demonstrates that internal fast ion interface modification is an indispensable innovative feature. Comparing Example 14, Example 1, and Comparative Example 4, the conclusion is that only the outer layer of physically composite MXene exhibits severe stacking, poor interface bonding, and a lack of internal conductive network defects, resulting in performance far inferior to the in-situ covalently anchored MXene five-layer system of this invention, fully validating the creativity and necessity of the original MXene structure of this invention.

[0089] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A composite silicon-carbon anode material, characterized in that, The silicon-carbon anode material is a micron-sized spherical composite particle, and each particle has a functional composite structure, including: a porous carbon matrix layer, a two-dimensional conductive layer, a silicon-based active material layer, a fast ion conductor thin film layer, and a conductive carbon coating layer. The porous carbon matrix layer has multi-level interconnected channels inside; The two-dimensional conductive layer is grown in situ on the inner wall of the multi-level interconnected channels and is anchored to the porous carbon matrix layer by covalent bonds. The silicon-based active material layer is confined and deposited within the multi-level interconnected channels after the growth of the two-dimensional conductive layer, and forms a covalent interface with the two-dimensional conductive layer. The fast ion conductor thin film layer is continuously coated on the surface of the two-dimensional conductive layer, the surface of the silicon-based active material, and the inner wall of the multi-level interconnected channels.

2. The composite silicon-carbon anode material according to claim 1, characterized in that, The porous carbon matrix layer simultaneously comprises interconnected macropores, mesopores, and micropores, with a D50 of 5–15 μm and a specific surface area of ​​600–2400 m². 2 / g, total pore volume is 0.8–2.2 cm³ 3 / g; The two-dimensional conductive layer comprises Ti3C2T x MXene nanosheets, wherein the MXene nanosheets are bonded to the porous carbon matrix via covalent bonds of Ti-OC; The silicon-based active material includes silicon nanocrystals, which are uniformly and confinedly deposited in the internal interconnected channels modified with MXene. The original particle size of the silicon nanocrystals is 0.1–120 nm, and a Ti-O-Si covalent interface is formed between the silicon nanocrystals and the MXene nanosheets. The thickness of the fast ion conductor thin film layer is 1 to 6 nm, and the material of the fast ion conductor thin film layer includes at least one of lithium phosphorus oxy nitrogen, lithium titanium phosphate, lithium aluminum phosphate, or lithium lanthanum zirconium. The conductive carbon coating layer has a thickness of 10–35 nm and coats the outer surface of the micron-sized spherical composite particles.

3. The composite silicon-carbon anode material according to claim 1, characterized in that, The silicon-carbon anode material comprises, by mass percentage: 10-80% porous carbon matrix layer, 0.8-4% two-dimensional conductive layer, 10-80% silicon-based active material layer, 0.5-4% fast ion conductor thin film layer, and 1.5-8% conductive carbon coating layer, with the sum of the mass percentages of each component being 100%.

4. The composite silicon-carbon anode material according to claim 2, characterized in that, The macropores have a diameter of 50–200 nm, the mesopores have a diameter of 2–50 nm, and the micropores have a diameter of 0.35–2 nm; the micropores account for 5–100% of the total pore volume, the mesopores account for 5–100% of the total pore volume, and the macropores account for 5–50% of the total pore volume, with the sum of the three percentages being 100%.

5. The composite silicon-carbon anode material according to claim 2, characterized in that, The MXene nanosheets have a thickness of 1–5 nm and a lateral dimension of 1–80 nm.

6. A preparation method for preparing the composite silicon-carbon anode material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of porous carbon matrix layer: The carbon source precursor is mixed with the pore-forming agent to form a precursor slurry, which is then spray-dried to obtain composite carbon precursor microspheres. The composite carbon precursor microspheres are pre-carbonized and shaped to obtain a carbon skeleton semi-finished product. The carbon framework semi-finished product is calcined with an activator to create pores, and then purified by post-treatment to obtain a porous carbon matrix; S2. Porous carbon channel alumina pre-activation modification: Alumina modification layer is deposited on the inner wall of the channel or the surface of MXene nanosheets by atomic layer deposition; S3. In-situ confined deposition of nano-silicon inside the pores: Nano-silicon grains are deposited inside the pores using chemical vapor deposition. S4. In-situ coating of fast ion conductors: A continuous fast ion conductor film is generated in-situ on the surface of nano-silicon grains, the surface of MXene nanosheets, and the inner wall of the channels. S5. Conductive carbon composite coating on the outer layer of the powder: A conductive carbon coating layer is formed on the outer surface of the particles through gas phase carbon coating and / or liquid phase carbon coating processes to obtain the silicon-carbon anode material.

7. The preparation method according to claim 6, characterized in that, The carbon source precursor includes thermosetting phenolic resin and mesophase pitch; The pore-forming agent comprises polyethylene glycol PEG2000 and nano-calcium carbonate in a mass ratio of (1-6):(6-1); The mass ratio of the thermosetting phenolic resin, mesophase pitch and pore-forming agent is (40-70):(10-40):(1-20); The inlet air temperature of the spray dryer is 120-220℃ and the outlet air temperature is 65-120℃. The pre-carbonization and shaping temperature is 500–950℃, and the holding time is 2–8 hours; The mass ratio of the carbon skeleton semi-finished product to the activator is (1-6):(6-1), the calcination temperature is 600-1050℃, and the holding time is 1-6h; The activator comprises KOH and ZnCl2 in a mass ratio of (1-10):(10-1).

8. The preparation method according to claim 6, characterized in that, In step S1, the preparation of the porous carbon matrix layer further includes the following steps: A porous carbon matrix prepared from S1 is spread evenly in a rotary vapor furnace, with a single layer thickness ≤2 mm; argon gas is continuously purged from the furnace cavity, with the oxygen content controlled to <10 ppm, and the temperature is raised to 700-900℃; Ti3AlC2T is then introduced. x Precursor vapor, carrier gas Ar flow rate 60-120 sccm, vapor phase permeation 1.5-3 h; the precursor gas source is turned off, furnace temperature is maintained at 700-900℃, LiF-HCl composite vapor phase etching system is introduced, and etching is carried out at this temperature for 2-4 h; high-purity argon gas is continuously purged into the furnace cavity to completely remove residual etching byproducts; after purging, argon gas is continuously introduced and the furnace is naturally cooled to room temperature, and the material is discharged in a sealed manner to obtain a porous carbon matrix with an embedded MXene three-dimensional conductive network, which is preserved in complete isolation from water and oxygen.

9. The preparation method according to claim 6, characterized in that, Step S2 includes: placing the porous carbon matrix in an atomic layer deposition chamber, evacuating to below 5 Pa, heating to 180–320 °C, using trimethylaluminum and water vapor as precursors, and 99.999% high-purity nitrogen as carrier gas and purge gas, cycling 5–40 times, and depositing a 0.5–4 nm alumina modification layer on the surface of MXene nanosheets and the inner wall of the pores; Step S3 includes: spreading the powder obtained in step S2 in a single layer on a rotary CVD furnace boat with a layer thickness ≤2 mm, replacing the oxygen content with argon until the oxygen content is <10 ppm, heating to 420-580℃ and holding for 0.5 h, introducing a mixed gas with a SiH4 to Ar volume ratio of 1:(15-40) at a gas flow rate of 50-150 sccm, and depositing for 60-400 min; Step S4 includes: transferring the powder obtained in step S3 into a plasma-assisted atomic layer deposition furnace, with a vacuum degree ≤3 Pa and a temperature of 250-400℃, and using alternating pulsed cycles of organometallic lithium sources, titanium sources, and phosphorus sources for 5-35 cycles to generate a 1-6 nm lithium titanium phosphate fast ion conductor film in situ on the surface of nano-silicon grains, the surface of MXene nanosheets, and the inner wall of pores; wherein the organometallic lithium source is selected from one or more of LiOtBu, LiHMDS, and Lider, the titanium source is selected from one or more of Ti[NMe2]4, Ti(OiPr)4, and TiCl4, and the phosphorus source is selected from one or more of trimethyl phosphate and triethyl phosphate; Step S5 includes: using one or more of methane and its homologues, acetylene and its homologues, and benzene and its homologues as carbon source gases, and using one or more of helium, argon, and nitrogen as inert gases, with the ratio of inert gas to carbon source gas being (1-10):1, the rotary kiln speed being 0.25-2.5 r / min, the heating rate being 1-10℃ / min, the deposition temperature being 500-950℃, and the deposition time being 1-6 h.

10. A lithium-ion battery, characterized in that, Includes positive electrode, negative electrode, separator and electrolyte; The negative electrode sheet comprises a composite silicon-carbon negative electrode material as described in any one of claims 1-5.